PEMBACAAN KRITIK SASTRA FEMINIS TERHADAP BEBERAPA NOVEL INDONESIA MODERN - -, Wiyatmi (Diksi, 2015)
This article is about a study describing several writers’ perspectives toward the phenomenon of polygamy based on some novels of theirs and the ideology of feminism serving as the background of the perspectives. The novels studied are Fira Basuki’s Biru, Abidah Al-Khalieqy’s Geni Jora and Perempuan Berkalung Surban, and Dewi Sartika’s Dadaisme. The result of the study indicates the following. (1) There are three patterns of polygamy in the novels. The polygamy in Al-Khalieqy’s Geni Jora and Sartika’s Dadaisme is conducted openly with the first wife’s permission, her inability to have a baby being the cause, and both wives have good mutual relationship. The polygamy in Al-Khalieqy’s Perempuan Berkalung Surban is also conducted openly but with the first wife forced to give permission, the husband not living in harmony with the first wife and having a love affair resulting in the other woman’s pregnancy being the cause, and the wives do not have good mutual relationship. The polygamy in Fira Basuki’s Biru is hidden polygamy, that is, without the first wife’s permission, with her relationship with the second wife not being good and that with her husband not having been good, either, causing him to commit the adultery. (2) Based on the novels, the writers’ perspectives toward polygamy are as follows. Abidah Al-Khalieqy’s views polygamy as an emergency and it can be conducted with some requirements being met, among which are economical condition and a sense of justice, which are to be seriously considered. If the husband cannot fulfil the requirements, disharmonious relationship will occur, resulting in divorce. Fira Basuki tends to reject polygamy, viewing the husband concerned as doing some injustice. The possible resulting hate in the first wife toward her husband and the second wife may result in conflict and divorce. Dewi Sartika allows polygamy, depicting characters who can love more than one person (and consequently commit adultery). (3) There are two streams of feminism serving as the background of the writers’ perspectives: radical feminism, reflected in the works of Al-Khalieqy and Fira Basuki, and liberal feminism, reflected in the work of Dewi Sartika. Radical feminism views polygamy as a form of male domination over females that results in family problems. Liberal feminism tends to allow polygamy as a form of patriarchal domination; those committing polygamy do not always have problems resulting from it and polygamy can be a solution for the problem of not being able to have a child from the first wife. Keywords: polygamy, female writers, feminism